Implication of DNA Methylation Profiling in Oral Epithelium for Lung Cancer Screening. (26th November 2012) - Harada, Hiroaki; Miyamoto, Kazuaki; Yamashita, Yoshinori; Nakano, Kikuo; Taniyama, Kiyomi; Kimura, Masami; Miyata, Yoshihiro; Ohdan, Hideki; Okada, Morihito
Abstract : In lung cancer, the roles of molecular alterations in blood, sputum, bronchial brushing, and exhaled gas samples, which are relatively easy to obtain, have been evaluated for clinical availability. This study was based on the hypothesis that similar molecular alterations occur in the lung and oral cavity because both are exposed to the same environmental or tobacco-derived carcinogens. Because epigenetic alterations due to exposure to carcinogens are thought to play a major role in the development of lung cancer, the DNA methylation status of 11 genes in the oral epithelium was analyzed in lung cancer patients (n = 16 ) and control individuals without lung cancer (n = 32 ). DNA methylation profiling revealed that GDNF, RARB, and HS3ST2 were methylated more frequently in cancer patients than in the control participants (P = 0.0017, 0.0062, and 0.0193, resp.). Combined analysesindicatedthat 6 of 16 cancer patients (37.5%), but only 1 of 32 control individuals (3.1%) showed DNA methylation in 2-3 of these 3 genes (P = 0.0015 ). These combined analyses showed the high specificity and positive predictive value in total and subgroup analyses. Our data suggest that DNA methylation profiling using oral epithelium may help in the identification of individuals with a high risk of lung cancer.